Impact of PCB ground plane size on dual-band antenna performance - Zhang, Lin (2013)
In this paper, a novel dual-band antenna for wireless local area networks (WLAN) application is designed and simulated. Firstly, a standalone dual-band antenna on a smaller PCB is designed and satisfactory radiation patterns at 2.4 GHz and 5.2 GHz are achieved. Then, the antenna is integrated on a larger PCB and it is found that the radiation patterns become unsatisfactory, in particular at 5.2 GHz. In order to improve the radiation patterns, four slots are cut on the ground plane. The dual-band antenna consists of a meander strip for 2.4 GHz and a quarter-ring for 5.2 GHz, both printed on FR4 substrate with thickness of 0.8 mm. The final dual-band antenna with the four slots on the ground plane attains 9.3% impedance bandwidth and 1.9 dBi gain at 2.4 GHz, and 16% impedance bandwidth and 3.4 dBi gain at 5.2 GHz, respectively.